Assessment of nitrogen and phosphorus flows in the brazilian beef Agroecosystem - Rezende, Vanessa Theodoro (2025)
This thesis examined nitrogen and phosphorus flows in Brazilian beef cattle production systems, covering production, slaughter, and consumption stages, aiming to assess nutrient use efficiency, identify structural vulnerabilities, and evaluate management perspectives. Using a territorial metabolism approach based on material flow analysis, data on production, processing, distribution, and consumption across Brazilian states from 2011 to 2021 were integrated, combining statistical analysis and clustering to determine the trajectories of the system from a state-level perspective. Results identified three groups of states: scale-oriented systems, prioritizing production expansion over nutrient efficiency; traditional extensive systems, characterized by low productivity and consolidated structural barriers; and intensive systems, exhibiting the highest nutrient use efficiency, although not the highest herd or carcass production. This heterogeneity highlights the absence of a convergent national trajectory toward efficient nutrient management. Temporal analysis showed stagnation in nitrogen and phosphorus use efficiency, with no statistically significant annual effects detected. Structural vulnerabilities were identified, including Brazil′s reliance on imported phosphorus and urea, concentration of soybean production in a few regions, and interregional transport inefficiencies, increasing exposure to geopolitical and economic risks. Environmental implications varied according to production models: intensive systems achieved higher conversion efficiency but concentrated environmental pressures in smaller areas, whereas extensive systems remained inefficient, sustained by structural incentives such as low land costs, cheap labor, and land speculation dynamics. Post-animal production stages were more efficient than primary production, but consumption showed the lowest nutrient use efficiency due to food waste and nutrient losses through human excretion. Waste management infrastructure was underdeveloped, with limited adoption of biodigesters, insufficient composting, and inadequate characterization of produced manure. Overall, the results indicate that inefficiencies in the Brazilian beef supply chain are structural and technical. Improving nutrient management requires coordinated, long-term changes, including redesigning production systems to enhance nutrient cycling, strengthening environmental management in intensive systems, diversifying nutrient sources to reduce import dependency, expanding circular economy infrastructure, and aligning public policies with long-term efficiency goals. Future research priorities include detailed evaluation of manure management practices, quantification of nutrient losses during transport and storage, integration of greenhouse gas emissions into nutrient flow analyses, economic feasibility studies of circular technologies under Brazilian conditions, and regional characterization with enhanced zootechnical and management data. Finally, this study demonstrates that material flow analysis and territorial metabolism approaches are valuable diagnostic tools for identifying systemic inefficiencies and intervention opportunities, but their translation into practical improvements depends on public policies, sustained investment, and institutional coordination, underscoring that the main challenges in Brazilian beef cattle production are organizational, institutional, and in some regions technological.